Hubungan Dukungan Keluarga dan Tingkat Spiritual terhadap Kualitas Hidup Pasien Kanker Serviks - Anestiyah, Marisa Debby; Supriadi, Supriadi; Wahyuni, Rahmawati (JIDAN Jurnal Ilmiah Bidan, 2022)
Background : Cervical cancer is a malignant disease. The majority of cervical cancer patients have a low quality of life because of the disease they suffer. Family support and spiritual level are very important to improve the quality of life of cervical cancer patients. Purpose : This study was to determine the relationship between family support and spiritual level on the quality of life of cervical cancer patients. Method:This study uses an approach Cross Sectional. The number of cervical cancer patients undergoing chemotherapy at A.W. Sjahranie July-December 2021 as many as 162 patients. The sampling technique in this studypurposive sampling with a total sample of 115 people. Results:Test Somer’s D is obtained by the value of r (correlation coefficient) of 0.996 meaning that it has a very strong or perfect relationship. Meanwhile, the significance value of ρ is 0.036 <0.05 or ρ <α.Conclusion:There is a relationship between family support and spiritual level on the quality of life of cervical cancer patients at A.W. Hospital. Sjahranie.